EKSPLORASI KUBURAN TEPI PANTAI DESA PLAWANGAN, KECAMATAN KRAGAN, KABUPATEN REMBANG, JAWA TENGAH: KAJIAN TOPONIMI - Dwika Muzakky Anan Taturia; Multamia R.M.T. Lauder (Politeknik Negeri Jakarta, 2023)
Since archaeological excavations were carried out from 1977 to 1993 at the Plawangan site located on the coastal community of Plawangan Village, archaeologists suspected that this site was once a necropolis (a burial place from the first century AD). This research aims to explore the public seaside cemeteries in Plawangan Village, Kragan District, Rembang Regency, Central Java based on their necronym pattern (naming of a cemetery). This research also seeks to reveal further the existence of public seaside cemeteries in Plawangan Village during modern times by examining the collective memories and meanings of local inhabitants for the names of cemeteries. In this research, the data were collected from interviews using the Cakap Semuka Method by applying Rekam Catat Techniques, namely Migit, Mbedhodo, and Pohlendeh cemeteries. By utilizing a qualitative approach and descriptive method, the writer analyzed seaside necronyms based on Nyström's Theory of Presuppositional Meanings, namely categorical, associative, and emotive meanings. Categorically, the seaside cemeteries of Plawangan Village were influenced by myth and flora categories. From the morphophonemic process, the forms of seaside necronym are pre-fixations, ellipsis, and verb phrases. Meanwhile, based on identification of associative and emotive meanings show interesting findings about the meanings and perceptions of nowadays society regarding the reasons why there are public cemeteries were located near the beach, such as: (1) choosing the location of a public cemeteries near beach because it follows the past burial methods archaeological sites in coastal sandy soil which are believed to be able to preserve bones longer than other types of soil, (2) traces of the spread of Islam, (3) myths in society, (4) loss of the haunted impression of each grave, and (5) the haul tradition of respected religious figures.